2022
DOI: 10.3389/fphar.2022.830323
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antioxidant effects of natural compounds on H2O2-induced cytotoxicity of human monocytes

Abstract: Natural compounds are endowed with a broad spectrum of biological activities, including protection against Toxins. Most of them are known for their antioxidant and radical scavenging activities. However, the synergistic combination of these natural molecules is not well studied. Therefore, the present study aims first to investigate the effect of four potent natural molecules [rosmarinic acid (Ros-A), ellagic acid (Ella-A), curcumin (Cur), and syringic acid (Syr-A)] on H2O2 -induced cell cytotoxicity and oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, the efficiency of these compounds is usually studied individually, and their synergistic effects are lacking. Several studies have addressed the intracellular generation of ROS by human monocytes (TPH-1) cells [ 29 ], a well-known model for studying the effects of toxins and/or the development of new scavengers. Ben Mrid et al [ 29 ] employed TPH-1 cells as a model to evaluate the cytoprotective effect of four natural compounds and their mixtures on H 2 O 2 -induced oxidative stress, analyzing their potential molecular mechanisms to avoid H 2 O 2 -oxidative damage.…”
Section: Reactive Oxygen Species In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficiency of these compounds is usually studied individually, and their synergistic effects are lacking. Several studies have addressed the intracellular generation of ROS by human monocytes (TPH-1) cells [ 29 ], a well-known model for studying the effects of toxins and/or the development of new scavengers. Ben Mrid et al [ 29 ] employed TPH-1 cells as a model to evaluate the cytoprotective effect of four natural compounds and their mixtures on H 2 O 2 -induced oxidative stress, analyzing their potential molecular mechanisms to avoid H 2 O 2 -oxidative damage.…”
Section: Reactive Oxygen Species In Cancermentioning
confidence: 99%
“…Several studies have addressed the intracellular generation of ROS by human monocytes (TPH-1) cells [ 29 ], a well-known model for studying the effects of toxins and/or the development of new scavengers. Ben Mrid et al [ 29 ] employed TPH-1 cells as a model to evaluate the cytoprotective effect of four natural compounds and their mixtures on H 2 O 2 -induced oxidative stress, analyzing their potential molecular mechanisms to avoid H 2 O 2 -oxidative damage. Results showed that the addition of natural compounds, especially the synergistic effect of curcumin and rosmarinic acid, could act as cytoprotective and immunostimulant agents against H 2 O 2 -induced.…”
Section: Reactive Oxygen Species In Cancermentioning
confidence: 99%
“…Plant extracts and essential oils are among the many natural products that are used extensively across the world because of their antioxidant activity, which protects people against a variety of ailments brought on by oxidative stress (Aggrey et al, 2019;Sonam and Guleria, 2017;Srisuksomwong et al, 2023;Zulkefli et al, 2023). Synergistic interactions between various antioxidant chemicals in mixtures of synthetic and natural antioxidants, natural products, or mixtures of various herbal extracts or plant essential oils can increase antioxidant capacity (Basavegowda and Baek, 2021;Ben Mrid et al, 2022;Sharma et al, 2020). In this study, the same principle was applied to combinations of the extracts/ pure compounds from endophytic fungi.…”
Section: Introductionmentioning
confidence: 99%